Evaluating the efficiency of attractant lures for cucurbits fruit fly Dacus ciliatus (Loew) (Diptera: Tephritidae) - حمد, باسم; خلف, محمد; الربيعي, حسين; سلمان, عدنان; جمعة, حذيفة; عبد, احمد (Iraqi Journal of Science, 2025)
Laboratory and field experiments were conducted to measure the efficiency of the lures : Casein, Glycine , Albumin, 2Butanone and Cucurbit fruit extract to attract cucubits fruit fly Dacus ciliatus (Loew).Results of laboratory tests indicated that albumin lure was more efficient during the first 24 hrs with significant differences compared with other lures used. Field experiments confirmed the efficiency of albumin lure in comparison with other lures, using the local designed trap which was more efficient in fly capture than Jackson trap. Monitoring seasonal fluctuation in adults catched number during autumn season in Madain region indicated the presence of two peaks. The first one occurred at first week of September, while the second was at the first week of October.